2021
DOI: 10.1155/2021/9979560
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus Severity Classification Using Features Selection and Machine Learning Algorithms

Abstract: Keratoconus is a noninflammatory disease characterized by thinning and bulging of the cornea, generally appearing during adolescence and slowly progressing, causing vision impairment. However, the detection of keratoconus remains difficult in the early stages of the disease because the patient does not feel any pain. Therefore, the development of a method for detecting this disease based on machine and deep learning methods is necessary for early detection in order to provide the appropriate treatment as early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The epithelial features extracted from the OCT images were the most valuable for the discrimination process. 2021) also found that the RF outperformed the decision tree model (89% accuracy vs. 71%, respectively), while Aatila et al (2021) found the RF model to have the highest accuracy when compared with other ML models in detecting all classes of KC. AI has been used to screen potential candidates for refractive surgery besides detecting KC.…”
Section: Ai Application In Kcmentioning
confidence: 94%
“…The epithelial features extracted from the OCT images were the most valuable for the discrimination process. 2021) also found that the RF outperformed the decision tree model (89% accuracy vs. 71%, respectively), while Aatila et al (2021) found the RF model to have the highest accuracy when compared with other ML models in detecting all classes of KC. AI has been used to screen potential candidates for refractive surgery besides detecting KC.…”
Section: Ai Application In Kcmentioning
confidence: 94%
“…Castro-Luna et al [38] found that the random forest outperformed decision tree model (89% accuracy vs. 71%, respectively) based on tomographic and biomechanical variables. Cao et al [39] also found the random forest model outperformed other machine learning algorithms using tomographic and demographic data, while Aatila et al [40] found the random forest model to have the highest accuracy compared to other machine learning models trained on anterior segment (AS)-OCT images in detecting all classes of KCN including ffKCN.…”
Section: Methodsmentioning
confidence: 99%
“…We used the mean absolute SHAP values (|SHAP value|) to illustrate the global importance of features ( 39 ). The sequential forward feature selection approach was then employed to generate the optimal feature subset ( 40 ). The general practices in this bottom-to-top search method involved starting with an empty feature subset, adding one feature out of the remaining features in each iteration (the order of addition depended on the feature importance calculated by the SHAP values: the more important the feature was, the greater was the precedence it had), and then evaluating the pros and cons of the generated feature subset by using 10-fold cross-validation on the derivation cohort.…”
Section: Methodsmentioning
confidence: 99%